2014
DOI: 10.3390/v6072826
|View full text |Cite
|
Sign up to set email alerts
|

Membranous Replication Factories Induced by Plus-Strand RNA Viruses

Abstract: In this review, we summarize the current knowledge about the membranous replication factories of members of plus-strand (+) RNA viruses. We discuss primarily the architecture of these complex membrane rearrangements, because this topic emerged in the last few years as electron tomography has become more widely available. A general denominator is that two “morphotypes” of membrane alterations can be found that are exemplified by flaviviruses and hepaciviruses: membrane invaginations towards the lumen of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
246
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(253 citation statements)
references
References 161 publications
(256 reference statements)
6
246
1
Order By: Relevance
“…During viral replication, the capsid proteins appeared spread throughout the entire cytoplasm, in contrast to the intermediate dsRNA species, which were predominantly located close to the nucleus and organized in large structures. This particular intracellular distribution in large clusters suggests that the viral replication occurs in membranous factories, as proposed for other plus-strand RNA viruses, such as the hepatitis C and Dengue virus [25]. …”
Section: Discussionmentioning
confidence: 82%
“…During viral replication, the capsid proteins appeared spread throughout the entire cytoplasm, in contrast to the intermediate dsRNA species, which were predominantly located close to the nucleus and organized in large structures. This particular intracellular distribution in large clusters suggests that the viral replication occurs in membranous factories, as proposed for other plus-strand RNA viruses, such as the hepatitis C and Dengue virus [25]. …”
Section: Discussionmentioning
confidence: 82%
“…For instance, hepatitis C virus, brome mosaic virus (BMV) and tobacco mosaic virus replicate in association with endoplasmic reticulum (ER) membranes. In contrast, Flock House virus and carnation Italian ringspot virus replicate in mitochondria, whereas tomato bushy stunt virus replicates in peroxisomes (den Boon et al, 2010;Laliberté and Sanfaçon, 2010;Paul and Bartenschlager, 2013;Romero-Brey and Bartenschlager, 2014). However, the mechanisms by which viruses target their replication proteins to particular membranes for VRC assembly are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus is known to induce accumulations of vesicles forming a membranous web (MW) (26), consisting of mainly double membrane vesicles (DMVs) that are thought to be the site of viral RNA replication within the infected liver (27,28). To examine whether MWs are formed in vivo within the liver of NPHV + horses, we performed electron microscopy (EM)-based studies on liver biopsies of an infected horse, and in various cells, we observed numerous vesicles (Ve), which could not be detected in an uninfected horse ( Fig.…”
Section: Horses Can Be Experimentally Infected With Nphv and Display mentioning
confidence: 99%